2018
DOI: 10.1159/000490702
|View full text |Cite
|
Sign up to set email alerts
|

Do Common Marmosets (Callithrix jacchus) Use Scent to Communicate Information about Food Resources?

Abstract: Many animals use olfactory cues to signal information about food resources; however, this particular use of scent has received little attention in primates. Common marmosets (Callithrix jacchus) are exudativores that gouge bark to elicit exudate production and frequently deposit scent marks at gouge holes. We conducted preliminary tests of the hypothesis that common marmosets use olfactory cues to communicate information about exudate value, with more desirable resources targeted for marking. We performed choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…(Which would be difficult in the field due to the multitude of variables impacting feeding decisions.) Our findings demonstrate the interplay between physiology and behavior in foraging decisions: animals deposited more scent marks on substrates with more food, and exposure to scent cues led to increased gouging behavior (Thompson et al, ). This suggests that animals may use scent as a means to identify more profitable gouge holes.…”
Section: Empiricism Rules Biology: Joining Lab and Field Approaches Rmentioning
confidence: 61%
See 1 more Smart Citation
“…(Which would be difficult in the field due to the multitude of variables impacting feeding decisions.) Our findings demonstrate the interplay between physiology and behavior in foraging decisions: animals deposited more scent marks on substrates with more food, and exposure to scent cues led to increased gouging behavior (Thompson et al, ). This suggests that animals may use scent as a means to identify more profitable gouge holes.…”
Section: Empiricism Rules Biology: Joining Lab and Field Approaches Rmentioning
confidence: 61%
“…Although our collaboration grew out of happenstance, it has persisted because the collaborative benefits bridge conventional challenges for studying primate adaptations. Proof of benefit is apparent in the breadth of projects spanning the ecological physiology of feeding in howlers (Williams et al, ; Vinyard et al, , 2012), thermoregulation in tropical and temperate monkeys (Thompson et al, , 2016, Thompson, Scheidel, Glander, Williams, & Vinyard, , Thompson, Powell et al, ) and the sensory ecology underlying scent‐marking in marmosets (Bottenberg et al, ; Thompson et al, ). Despite the seeming lack of congruity at first glance, we can portray each project as trying to understand the ecological physiology of primates.…”
Section: Embracing Happenstance: Great Collaborations Can Start By Chmentioning
confidence: 99%
“…Lastly, an experimental study showed that two captive common marmosets scent-marked substrates with highvalue foods more than substrates with low-value foods, and they revisited these high-valued substrates more than low-valued ones [Thompson et al, 2018]. The available evidence supports that exudativorous primates scentmark more profitable exudate holes, which may be a behavioural strategy to increase foraging efficiency in patches with complex spatiotemporal resource availability.…”
Section: Discussionmentioning
confidence: 86%
“…However, some of the social information that lemurs use may not be apparent to human observers, as in the case of olfactory cues. Marmosets, for example, may use scent-marking to indicate high-value food resources for conspecifics [Thompson et al, 2018]. Future research should attempt to investigate additional possible cues to further evaluate the role of social learning in food choice.…”
Section: Discussionmentioning
confidence: 99%